Design, Synthesis, Biological Evaluation, And Molecular Docking Studies Of Ortho-Carboxamido Stilbenes As Anti-Diabetic And Anti-Proliferative Agents - Mohamad, Norhadi (2022)
A total of eleven ortho-carboxamido stilbenes (50a-50k) in 63-83 % yield have been synthesized using our modified Heck coupling method, and characterized using FT-IR, NMR, and HRMS. The research started with the Wittig reaction of 3,5-dimethoxybenzaldehyde (45) and methyltriphenylphosphonium iodide to form 3,5-dimethoxystyrene (46) followed by the Heck reaction with amide derivatives (49) under basic conditions to provide the corresponding (E)-stilbene derivatives (50a-50k). Five ortho-carboxamido stilbenes (50a-50e) were subjected to anti-diabetic studies on α-amylase and α-glucosidase enzymes.